Cell wall remodeling in a fungal pathogen is required for hyphal growth into microspaces - Hinata Miki; Melani Mariscal Gomez; Ayaka Itani; Daisuke Yamanaka; Yoshikatsu Sato; Antonio Di Pietro; Norio Takeshita (mBio)
ABSTRACT Hyphae are filamentous structures that are crucial for the lifestyle of many fungi, allowing rapid colonization of diverse substrates such as dead organic material or living host tissue. One of the key features of fungal hyphae is their remarkable morphogenetic plasticity. During host colonization, phytopathogenic fungi must traverse extremely narrow spaces between plant cells such as the apoplastic space or the plasmodesmata. The mechanisms underlying hyphal plasticity during growth into microspaces are poorly understood. Here, we tested a set of isogenic mutants of Fusarium oxysporum, an important plant pathogen that causes devastating vascular wilt diseases on more than a hundred crops, for their ability to cross extremely narrow 1 µm channels, approximately one-quarter the width of hyphae. We found that the conserved Mpk1 cell wall integrity mitogen-activated protein kinase (MAPK) cascade is required for efficient growth of hyphae through the microchannels, whereas the two other MAPK pathways, the Fmk1 invasive growth and the Hog1 hyperosmolarity response cascades, are dispensable for this process. Staining with specific probes showed a reduction in both chitin and glucan content in the cell wall of hyphae growing within the 1 µm channel. We further establish that channel passage in cell wall remodeling mutants is impaired due to their inability to constrict hyphal diameter, and this defect can be rescued by increasing extracellular osmolarity. Both the cell wall integrity mutants impaired in microchannel passage, as well as the invasive growth mutants unable to penetrate cellophane membranes, caused significantly reduced mortality in tomato plants. Our study reveals that two morphogenetic processes essential for plant infection, which are governed by distinct cellular pathways, contribute independently to fungal phytopathogenicity.IMPORTANCEThis study highlights the critical role of hyphal plasticity and cell wall remodeling in the pathogenicity of Fusarium oxysporum, a major plant pathogen affecting over a hundred crops. The ability of fungal hyphae to traverse narrow plant tissue spaces, such as apoplastic gaps and plasmodesmata, is essential for successful host colonization. The research demonstrates that the Mpk1 mitogen-activated protein kinase (MAPK) pathway, responsible for cell wall integrity, is crucial for hyphal growth through microspaces, while other MAPK pathways are not. Staining with specific probes showed a reduction in both chitin and glucan content in the cell wall of hyphae growing within 1 µm width channels. Both the cell wall integrity mutants impaired in microchannel passage, as well as the invasive growth mutants unable to penetrate cellophane membranes, caused significantly reduced mortality in tomato plants. Our study reveals that two morphogenetic processes essential for plant infection, which are governed by distinct cellular pathways, contribute independently to fungal phytopathogenicity.